INTEGRASI TEORI SISTEM KELUARGA MURRAY BOWEN DAN TEORI MASLAHAH TERHADAP DAMPAK MULTIDIMENSI LEMAH SYAHWAT BAGI KEHARMONISAN KELUARGA - Sugitanata, Arif (UIN Palopo, 2024)
This study aims to analyze the multidimensional impact of erectile dysfunction on family harmony using Murray Bowen's family systems theory and the theory of maslahah within the context of Islamic law. A harmonious family is ideal for any family unit, where each member feels happy, safe, and comfortable. However, achieving such harmony is not without challenges, one of which is erectile dysfunction, which can exert significant pressure on family relationships. Erectile dysfunction affects not only the physiological aspect of the sufferer but also has psychological and social repercussions, such as feelings of shame, loss of self-confidence, and severe stress that can lead to tension within relationships. This research employs a literature review method with descriptive-analytic analysis techniques. Primary data sources include books, journals, and relevant websites. Bowen's family systems theory is utilized to understand how erectile dysfunction can influence family dynamics, including concepts such as self-differentiation, triangulation, and family projection processes, and the theory of maslahah aids in finding holistic solutions to the impact of erectile dysfunction by emphasizing individual and family well-being in psychological, social, and health aspects. The findings indicate that erectile dysfunction exacerbates family dynamics by increasing emotional stress, altering power patterns, and causing negative projection and triangulation in relationships. From the perspective of maslahah, erectile dysfunction disrupts the well-being of individuals and families, necessitating a holistic approach that includes medical treatment and emotional support, as well as reducing social stigma. Therapeutic strategies that enhance self-differentiation, manage triangulation, and foster open communication between partners are crucial for maintaining family harmony. The integration of comprehensive medical care and support from family and the community is expected to help sufferers cope better with this condition and maintain harmony.